1996
DOI: 10.1089/dna.1996.15.817
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of m-ehk2 from the Murine Inner Ear, an eph Family Receptor Tyrosine Kinase Expressed in the Developing and Adult Cochlea

Abstract: To identify receptor tyrosine kinases (RTKs) present in the murine inner ear, a degenerate polymerase chain reaction (PCR) methodology was employed to clone partial cDNAs encoding RTKs from embryonic day-17.5 mouse whole inner ear RNA. At least 20 distinct TKs were identified within the first 50 subcloned PCR products obtained by this analysis (Davis/Lee et al., 1996). One of the receptor RTKs identified encoded an eph-related kinase not previously described in the mouse. Analysis of full-length cDNAs revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The mammalian inner ear is a structure that develops from a simple, epithelial sac to a highly complex labyrinth comprising five vestibular organs (the utricular and saccular maculae and the three cristae ampullares) that regulate balance, and the coiled, snail-shaped cochlea that regulates hearing. Several studies have reported the expression of various Eph molecules in the early embryonic inner ear (Ciossek et al, 1995;Lee et al, 1996;Henkemeyer et al, 1994;Pickles and van Heuman, 1997; Bianchi and Gale, 1998). However, the role of the Eph family in inner ear development is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mammalian inner ear is a structure that develops from a simple, epithelial sac to a highly complex labyrinth comprising five vestibular organs (the utricular and saccular maculae and the three cristae ampullares) that regulate balance, and the coiled, snail-shaped cochlea that regulates hearing. Several studies have reported the expression of various Eph molecules in the early embryonic inner ear (Ciossek et al, 1995;Lee et al, 1996;Henkemeyer et al, 1994;Pickles and van Heuman, 1997; Bianchi and Gale, 1998). However, the role of the Eph family in inner ear development is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the presence of several Eph family members in the developing inner ear (Ciossek et al, 1995;Lee et al, 1996;Henkemeyer et al, 1994;Pickles and van Heuman, 1997;Bianchi and Gale, 1998) and mature cochlea (Lee et al, 1996;Bianchi and Gale, 1998). In the present study, the immunohistochemical localization of two ephrin-A ligands and three EphA receptors was examined in developing and mature vestibular and cochlear regions of the inner ear using available antisera.…”
mentioning
confidence: 81%
“…Another family of proteins, ephrins and Eph receptors, acting through forward or reverse signaling pathways, have also been proposed to play a critical role in patterning auditory innervation (Bianchi and Gale, 1998;Lee et al, 1996;Pickles, 2003). EphB receptors in particular have been shown to influence the outgrowth of SAG fibers in vitro through interaction with ephrin-B1 (Bianchi and Gray, 2002), and disruption of EphB/ ephrin-B interactions results in aberrant cochlear innervation patterns (Zhou et al, 2011).…”
Section: Other Molecules Involved In Neuritic Extensionmentioning
confidence: 99%
“…Another family of proteins, ephrins and Eph receptors, acting through forward or reverse signaling pathways, have also been proposed to play a critical role in patterning auditory innervation (14,16,90,126,127). Especially, EphB receptors have been shown to influence outgrowth of SAG fibers in vitro through interaction with ephrin-B1 (15), and disruption of ephrin-B/EphB interactions results in aberrant cochlear innervation patterns (197).…”
Section: Axon Outgrowth and Extensionmentioning
confidence: 99%